Pelaksanaan Penanaman Nilai Karakter Religius, Disiplin, dan Rasa Ingin Tahu pada Pembelajaran Pendidikan Agama Islam di SMAS PGRI Rumpin - Nahiyatu Diniyah; Santi Lisnawati (Tarbiatuna: Journal of Islamic Education Studies, 2023)
This study aims to describe the implementation of inculcating religious character values, discipline, and curiosity in Islamic religious education learning at SMAS PGRI Rumpin and to find out what obstacles exist in planting character values in Islamic religious education learning. This research is a qualitative research. The research subjects are the curriculum, PAI teachers, and students. Using data collection techniques by observation, interviews, and documentation. In analyzing the data, the researcher used qualitative analysis techniques with the steps of data collection, data reduction, data presentation, and drawing conclusions and verification. The results of the research findings indicate that the implementation of character values ​​in learning Islamic religious education is through a program to strengthen character education in schools, namely religious character, discipline and curiosity because before the start of learning. Students carry out tadarus, pray and pray before learning, and come on time at the time of learning, read the material to be studied and are given pus-pus/advice on positive habits so that in students religious character, discipline, and sense of belonging are formed. want to know as written in the teacher's curriculum and lesson plans. Meanwhile, the obstacle starts from the parental factor. Keywords: inculcation of character values, character education, Islamic religious education